Braving Troubled Waters Sea Change in a Dutch Fishing Community - van Ginkel, Rob (MARE Publication Series, 2009)
Dwindling fish stocks, changing markets and often ill-advised government intervention have affected the lives of Dutch fishermen for decades. The author of this study has spent years among the fishermen of the Dutch island of Texel, and this book records the changes in their working lives, tracking the influence of national and international factors on the social and cultural structures of the community.